spn-F encodes a novel protein that affects oocyte patterning and bristle morphology in Drosophila. - Abdu, U.; Bar, D.; Schupbach, T. (Development, 2006)
The anteroposterior and dorsoventral axes of the Drosophila embryo are established during oogenesis through the activities of Gurken (Grk), a Tgfalpha-like protein, and the Epidermal growth factor receptor (Egfr). spn-F mutant females produce ventralized eggs similar to the phenotype produced by mutations in the grk-Egfr pathway. We found that the ventralization of the eggshell in spn-F mutants is due to defects in the localization and translation of grk mRNA during mid-oogenesis. Analysis of the microtubule network revealed defects in the organization of the microtubules around the oocyte nucleus. In addition, spn-F mutants have defective bristles. We cloned spn-F and found that it encodes a novel coiled-coil protein that localizes to the minus end of microtubules in the oocyte, and this localization requires the microtubule network and a Dynein heavy chain gene. We also show that Spn-F interacts directly with the Dynein light chain Ddlc-1. Our results show that we have identified a novel protein that affects oocyte axis determination and the organization of microtubules during Drosophila oogenesis.